(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
In the operation of hydrokinetic turbines in tidal sites, the effect of onset flow turbulence on device performance and reliability deserves particular attention. Computational Fluid Dynamics (CFD) models capable to describe this complex phenomenology are necessary to predict harmful operating conditions and to implement design strategies to mitigate the impacts. Similarly, the description of the interaction between turbine wakes and eddies in the onset turbulent flow is important in the study of tidal arrays. An original CFD methodology to simulate the operation of a tidal turbine in an arbitrary turbulent flow is presented. The methodology falls within the class of Synthetic Methods (SM). A randomly fluctuating velocity field is generated by a volume force distribution acting as forcing term in the Navier-Stokes equations. With respect to existing volume-force SM, an original definition of the forcing terms, and a control strategy to enforce a prescribed turbulence metrics are proposed. Volume force terms are imposed in a thin layer in the upstream region of the computational domain by a sinusoidal distribution with random variation of both intensity and phase. A Proportional-Integral-Derivative (PID) control is applied to minimize the difference between the intensity of the generated flow turbulence and the prescribed conditions. In [1] the model was applied to describe a turbulent stream in an unbounded flow by Detached Eddy Simulation (DES). The capability to generate eddies that evolve into a homogeneous, isotropic turbulent flow was demonstrated. Here, the model is applied to analyze the interaction between the generated onset turbulent flow and a tidal turbine. A computationally efficient approach is used here in which the turbine is described by a volume force method, in a similar fashion as turbulence generation is modelled. Specifically, a hybrid viscous/inviscid methodology is applied in which the DES solver is strongly coupled with a Boundary Integral Equation Method (BIEM) solver. At each time step, the blade load distribution is calculated by a time-accurate BIEM solution and recasts as volume force terms that are plugged into the DES solution. Examples of BIEM validation studies are given in [2, 3, 4] and in the results of a recent blind-test benchmark to be presented at the EWTEC 2023 Conference [5]. The numerical application described here deals with a 3-bladed horizontal-axis tidal turbine in a 16% intensity, isotropic turbulent onset flow. In the full paper, the overall methodology is described, and numerical results are presented and discussed. Particular attention is given to characterize the generated turbulent stream in terms of key metric quantities like turbulence intensity, Power Spectral Density (PSD), time and spatial scales, isotropy, Probability Density Function (PDF). The results are analyzed to discuss the capability of the methodology to render a physically-consistent description of the phenomenology governing turbine operation in a real tidal flow. • Gregori, M. et al., Mar. Sci. Eng. 2022. (https://doi.org/10.3390/jmse10101332) • Sarichloo, Z. et al., Marine Energy Journal, 2022. (https://doi.org/10.36688/imej.5.77-90) • Dubbioso, G.A. et al., Proceedings of EWTEC 2019. • Salvatore, F. et al., Mar. Sci. Eng. 2018, 6, 53. (https://doi.org/10.3390/jmse6020053) • Willden, R. et al., Submitted to EWTEC 2023.